Differences between Young Children's Actual, Self-perceived and Parent-perceived Aquatic Skills. Issue 5 (October 2021) - D'Hondt, Eva; Buelens, Lise; Barnett, Lisa M.; Howells, Kristy; Sääkslahti, Arja; Costa, Aldo M.; Jidovtseff, Boris; Mertens, Lisa; Martelaer, Kristine De
As drowning is a leading cause of unintentional injury/death in children worldwide, perceptions of their actual aquatic skills are of critical importance. Children's self-perceptions may influence the risks they take, and parental perceptions may influence the degree of supervision deemed to be necessary for children in and around water. Accordingly, we examined the differences between young children's actual, self-perceived and parent-perceived aquatic skills. Using a three-way repeated measures ANCOVA, we analyzed data from 134 child-parent dyads (56.0% boys; M age = 7.1, SD = 1.1 years; and 71.6% mothers). We measured self and parental perceptions of the child's aquatic skills with the 'Pictorial Scale of Perceived Water Competence' (PSPWC), and we applied the exact same 17 test items of the PSPWC to assess the child's actual aquatic skill level in the water. Controlling for years of swimming school experience, within-subject differences between the total scores on the 'Actual Aquatic Skills Test' (AAST) and both the child- and parent-completed PSPWC indicated lower than actual estimates of the children's aquatic skill level. The degree of disagreement against the AAST was more pronounced in parents than in 6-7 year-old children but was similar between parents and 8-9 year-old children, with these patterns being evident regardless of the children's sex. Our study contributes to an ongoing validation of the PSPWC and represents a key advance in assessing and comparing children's actual and perceived aquatic skill competence, using perfectly aligned instruments. Future research and practice might explore children's actual aquatic skills in different contexts (e.g., open water), include perspectives of non-parent caregivers and assess perceived and actual water competence across development.